Longitudinal tracking of healthcare professionals: a methodological scoping review - Yingxi Zhao; Xuan Li; Attakrit Leckcivilize; Mike English (BMC Medical Research Methodology)
Abstract Background Tracking and understanding the progress and experiences of health workers and the outcomes of workforce decisions are essential for evidence-based workforce planning. In this scoping review, we aim to identify longitudinal studies that prospectively tracked healthcare professionals and that specifically focused on workforce issues such as career preferences, choices, and working conditions, and summarise the different approaches and methods used for tracking. Methods We searched MEDLINE, Embase, Global Health, PsycINFO, CINAHL, Education Resource Information Center (ERIC), EconLit and the Cochrane Library for articles published between 2000–2022 that longitudinally tracked doctors, nurses, midwives, physician associates/assistants. We further compared articles and conducted a back-and-forward citation search to identify longitudinal tracking studies which sometimes have multiple published articles. We developed a typology of the different tracking approaches, and summarised the major areas assessed and tracked by different studies. Results We identified and analysed 263 longitudinal tracking studies. Based on population recruitment and follow-up methods, we grouped studies into seven categories (cohort studies, multiple-cohort studies, baseline and data linkage studies, baseline and short repeated measure studies, baseline-only studies, data linkage-only studies and repeated survey studies). The majority of studies included used a cohort or multiple-cohort design (n = 180), and several others also used data linkage (n = 45) and repeated measure approaches (n = 24). Sixty-two studies recruited participants while they were students and followed them until they became the active workforce, and nearly half of the included studies started directly from the active workforce stage. Most of the included studies examined workforce issues including employment status, preference or intention (to leave/remain/migrate, specific speciality or location etc.), and work environment, however there was a lack of widely used measurement tools for workforce issues. Additionally, nearly 40% examined wellbeing issues and a subset (20%) examined physical health in the context of workforce-related issues. Conclusion We described a large number of different healthcare professional longitudinal tracking studies. In order for longitudinal tracking to contribute to effective workforce planning, we recommend employing a mix of cohort and data linkage approaches to collect data across the different stages of the workforce ‘working lifespan’, and using and continuing to test standardised measurement instruments to better capture experiences related to workforce and wellbeing.